Investigation of JAKs/STAT-3 in lipopolysaccharide-induced intestinal epithelial cells. (1st August 2016) - Fu, L; Wei, L-W; Zhao, M-D; Zhu, J-L; Chen, S-Y; Jia, X-B; Lai, S-J
Summary: Janus-activated kinase (JAKs)-signal transducer and activator of transcription 3 (STAT-3) signalling play critical roles in immunoregulation and immunopathology, which involve inflammatory responses and enteritis. JAK phosphorylates STAT-3 in response to stimulation by cytokines or growth factors, and then activates or represses the gene expression. STAT-3 is activated persistently in cancer cells and contributes to the malignant progression of various types of cancer and inflammation. To elucidate the different roles of JAKs in the activation of STAT-3, the lipopolysaccharide-induced primary intestinal epithelial cell (IEC) acute inflammatory model was established. Small interference RNAs (siRNAs) were then employed to attenuate the expression levels of JAKs. Real-time quantitative reverse transcription–polymerase chain reaction (PCR) (qRT–PCR) revealed that JAK mRNA levels were reduced efficiently by JAK-specific siRNAs. Under the IEC inflammatory model transfected with si-JAK, which equates to effective silencing, qRT–PCR and Western blot assays, suggested that knockdowns of JAK attenuated the JAK-induced down-regulation of STAT-3 at the mRNA or protein levels. In particular, JAK1 played a key role, which was consistent with the RNA-Seq results. Subsequently, the expression levels of proinflammatory cytokines interleukin (IL)-1β and tumour necrosis factor (TNF)-α were down-regulated in the IEC inflammatory model transfected with si-JAK1. JAK1 appears as a direct activator for STAT-3, whereas treatments targeting JAK1 repressed STAT-3 sufficiently pathways in the IEC inflammatory model. Therefore, the control of JAK1 using siRNAs has the potential to be an effective strategy against enteritis. Graphical Abstract: